A Binary Solvent Dispersive Liquid-Liquid Microextraction Method for the Determination of Four Endocrine Disruptor Compounds by Gas Chromatography with Flame Ionization Detector - Yaman, Burcu; Zaman, Buse Tugba; Chormey, Dotse Selali; Bakirdere, Sezgin; Dilgin, Yusuf (SPRINGER INT PUBL AG, 2022)
The present study reports a precise and accurate binary dispersive liquid-liquid microextraction method for the enrichment of selected endocrine disruptor compounds for determination by gas chromatography flame ionization detector. Optimal variables of influential extraction parameters (binary solvent volume, disperser solvent volume, and vortex period) were determined with a design experiment. The main effects of these parameters were examined using analysis of variance (ANOVA), and the optimum parameters of the model were obtained from the model predictor. The analytes recorded detection limits varying between 0.43 and 2.7 ng/mL under the optimum experimental conditions. All the analytes exhibited good linearity and high precision (%RSD<10%) for six replicate measurements of the lowest calibration concentrations. The enhancement in calibration sensitivity for the analytes in GC-FID was found in the range of 41.9-64.5 times for each analyte by applying the developed method. The accuracy and feasibility of the method was assessed using water samples from a well and a hospital sewer, and the percent recovery results calculated using matrix matching calibration were in the range of 90-113%. These results demonstrated that the analytes can be accurately quantified in real aqueous matrices using the developed method.
Keywords: Endocrine disruptor compounds; Pesticides; Multivariate optimization; Binary solvent microextraction; DLLME; GC-FID; SOLID-PHASE EXTRACTION; MASS SPECTROMETRY; MULTICLASS PESTICIDES; MICRO-EXTRACTION; WASTE-WATER; GC-MS; ATRAZINE; FLUOXETINE; ALKYLPHENOLS; EXPOSURE; Environmental Sciences & Ecology; Meteorology & Atmospheric Sciences; Water Resources